Belgium : Selected Background Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1995)
This Selected Background Issues paper analyzes the competitiveness issues for Belgium and analyzes in what sense competitiveness is important for the country. The paper summarizes the approach followed in Belgium to measure developments in this respect. It discusses alternative indicators, including the current account of the balance of payments, and concludes that competitiveness is not currently a problem in Belgium. The paper also analyzes the rise in the current account surplus, and links it to the saving-investment balance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet